2000
DOI: 10.2337/diabetes.49.3.492
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physical mapping of a type 1 diabetes susceptibility gene (IDDM12) to a 100-kb phagemid artificial chromosome clone containing D2S72-CTLA4-D2S105 on chromosome 2q33.

Abstract: T ype 1 diabetes is an autoimmune disease characterized by the T-cell-mediated destruction of the insulin-secreting -cells of the pancreatic islets (1,2). It is a complex disease involving numerous susceptibility genes and environmental factors, which may act as triggers of the autoimmune response. Much research has been focused on identifying type 1 diabetes susceptibility genes in an effort to enhance the prediction of which individuals are at high risk of developing the disease, as well as to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…3 These results were confirmed in other populations such as Asians, populations of European ancestry, and Mexican-Americans. [11][12][13][14][15][16] Nevertheless, in other studies with populations of European ancestry, no evidence of association was found. [17][18][19][20] Recently, an association with a novel polymorphism at position 159 has been found in West African populations, but not in Chinese.…”
Section: Introductionmentioning
confidence: 77%
“…3 These results were confirmed in other populations such as Asians, populations of European ancestry, and Mexican-Americans. [11][12][13][14][15][16] Nevertheless, in other studies with populations of European ancestry, no evidence of association was found. [17][18][19][20] Recently, an association with a novel polymorphism at position 159 has been found in West African populations, but not in Chinese.…”
Section: Introductionmentioning
confidence: 77%
“…However, transmission disequilibrium test (TDT) analyses in a multiethnic population did not show an association with CD28 [123].…”
Section: Iddm12: Cytotoxic T Lymphocyte-associated Antigen (Ctla-4)mentioning
confidence: 93%
“…In addition, knowledge of the functional properties of CTLA-4 supports this possibility 169 and a single study did not find support for CD28 as the candidate gene of this region. 170 There is a microsatellite marker in the 3ЈUTR of the CTLA4 sequence, and several polymorphisms have been detected at CTLA4. 39 These polymorphisms, in particular the exon 1 (49 GϾA) SNP, have been investigated by TDT analysis in several populations, 41,140,[171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] and combined data sets from these large studies support linkage of the CTLA4 locus to T1D.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%